ANALISA KINERJA KEUANGAN PT. SUMBER ALFARIA TRIJAYA TBK DENGAN MENGGUNAKAN METODE ALTMAN Z – SCORE - Azlina, Yunidyawati (Jurnal Manajemen & Bisnis Jayakarta, 2022)
The purpose of this study was to determine the business continuity of PT. Sumber Alfaria Trijaya Tbk uses secondary data in the form of financial statements for 2017 – 2019. This study uses the Altman Z Score method, which is one method for assessing the performance of a company. The growth of the retail business has changed people's consumer behavior in meeting their needs. The COVID-19 pandemic condition also had an impact on the decline in the performance of the retail industry segment in 2017 ahead of the pandemic and in 2019 at the beginning of the pandemic. Z Score PT. Sumber Alfaria Trijaya Tbk in 2017 decreased from 1.14 in 2018 to -0.32. In 2019 the Z value increased rapidly to 1.26.